Antiviral Activity of Zinc Oxide Nanoparticles and Tetrapods Against the Hepatitis E and Hepatitis C Viruses - Gupta, Jyoti; Irfan, Minnah; Ramgir, Niranjan; Muthe, K. P.; Debnath, A. K.; Ansari, Shabnam; Gandhi, Jaya; Ranjith-Kumar, C. T.; Surjit, Milan (Frontiers in Microbiology, 2022)
Hepatitis E virus (HEV) causes an acute, self-limiting hepatitis. The disease takes a severe form in pregnant women, leading to around 30% mortality. Zinc is an essential micronutrient that plays crucial roles in multiple cellular processes. Our earlier findings demonstrated the antiviral activity of Zinc salts against HEV infection. Zinc oxide (ZnO) and its nanostructures have attracted marked interest due to their unique characteristics. Here we synthesized ZnO nanoparticles [ZnO(NP)] and tetrapod-shaped ZnO nanoparticles [ZnO(TP)] and evaluated their antiviral activity. Both ZnO(NP) and ZnO(TP) displayed potent antiviral activity against Hepatitis E and Hepatitis C viruses, the latter being more effective. Measurement of cell viability and intracellular Reactive Oxygen Species levels revealed that both ZnO(NP) and ZnO(TP) are noncytotoxic to the cells even at significantly higher dose, compared to a conventional Zinc salt (ZnSO4). Our study paves the way for evaluation of potential therapeutic benefit of ZnO(TP) against HEV and HCV.